2022
DOI: 10.1186/s12940-022-00898-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and drinking water intake of essential trace elements in a typical Kashin-Beck disease endemic area of Tibet, China

Abstract: Background: Essential trace elements (ETEs), such as copper (Cu), iron (Fe), manganese (Mn), molybdenum (Mo), selenium (Se), zinc (Zn), are very important elements for human health. Methods:In this study, 89 drinking water samples and 85 highland barleys were collected from 48 villages in 11 townships, and the average daily dose (ADD) of ETEs were calculated, in addition, health effects of ETEs to rural residents in Luolong County, a typical Kashin-Beck disease (KBD) endemic area in Tibet, were assessed. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(43 reference statements)
0
3
2
Order By: Relevance
“…These values were slightly lower than tsampa in non-Kashin-Beck-disease areas on the north bank of the Yarlung Zangbo River [42] (27.11 ± 3.44 mg•kg −1 ). They were not significantly different from the zinc concentration of Zha et al [43] in the Kashin-Beck disease areas of Tibet (23.58 ± 3.10 mg•kg −1 ). The average concentration of zinc in self-produced flour was 9.78 mg•kg −1 , ranging from 3.94-28.96 mg•kg −1 , which was lower than that of Guo et al [42] on both sides of the Yarlung Zangbo River (10.97 ± 4.67 mg•kg −1 in non-diseased areas on the north bank; 12.79 ± −1 1).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…These values were slightly lower than tsampa in non-Kashin-Beck-disease areas on the north bank of the Yarlung Zangbo River [42] (27.11 ± 3.44 mg•kg −1 ). They were not significantly different from the zinc concentration of Zha et al [43] in the Kashin-Beck disease areas of Tibet (23.58 ± 3.10 mg•kg −1 ). The average concentration of zinc in self-produced flour was 9.78 mg•kg −1 , ranging from 3.94-28.96 mg•kg −1 , which was lower than that of Guo et al [42] on both sides of the Yarlung Zangbo River (10.97 ± 4.67 mg•kg −1 in non-diseased areas on the north bank; 12.79 ± −1 1).…”
Section: Discussioncontrasting
confidence: 67%
“…These values were slightly lower than tsampa in non-Kashin-Beck-disease areas on the north bank of the Yarlung Zangbo River [42] (27.11 ± 3.44 mg•kg −1 ). They were not significantly different from the zinc concentration of Zha et al [43] in the Kashin-Beck disease areas of Tibet (23.58 ± 3.10 mg•kg −1 ).…”
Section: Discussioncontrasting
confidence: 67%
“…In some studies, many other trace elements including Sr, F, Fe, Cu, Mn, Co, and Zn are also associated with KBD; and Shi et al (2017) found that there were significant differences in the concentrations of certain trace elements (such as Se, Fe-Zn and Mo) in drinking natural water between KBD endemic areas and non-endemic areas. A study conducted in 2022 tested the intake of essential trace elements in diet and drinking water in typical KBD endemic areas found that the oral intakes of iron, manganese, and zinc in the whole township in the study area exceeded and slightly exceeded, respectively, and the average daily intakes of molybdenum, copper and especially selenium were generally low (Zha, An, Gao, et al, 2022). It has been suggested that arsenic, selenium, and thallium are three types of metal elements of high concern in parts of China, as a lack or excess of these elements in the diet can lead to a series of endemic diseases (Li, Xiao, & Zheng, 2012).…”
Section: Microelementmentioning
confidence: 95%
“…Low levels of selenium and iodine in the diet are considered to be the most important environmental factors contributing to disease (Xie, Liao, Yue, et al, 2018). In the past few decades, selenium and iodine supplementation to prevent KBD has been carried out in the endemic areas of China, and the results have been reported in many articles (Zha, An, Gao, et al, 2022;Yu , Qi, Shang, et al, 2019). Until now, it has not been determined whether selenium and iodine are initiating or conditioning factors in the pathogenesis of KBD.…”
Section: Microelementmentioning
confidence: 99%
See 1 more Smart Citation